基于遗传-二次规划法的封闭差动人字齿轮传动系统混合优化设计 - 朱增宝; 朱如鹏; 尹敏 (Jixie chuandong)
Using the positive transmission way of modified gear,a mathematical optimization model of the encased differential herringbone gear transmission system is set up by taking the lightest gear weight of this transmission system as the optimization objective.Taking the advantage of its optimization function of genetic algorithm and quadratic programming algorithm in MATLAB toolbox,the compound optimization design is carried out.The research results show that the problem of which the initial value of quadratic programming is difficult to determine is solved well by using the results of the genetic algorithm as the initial value of quadratic programming optimization.Compared with the genetic algorithm or quadratic programming,the optimization design variables of this compound optimization are obviously improved and the gear weight of the system is markedly reduced.The compound optimization method provides a simple and practical solution to obtain precise global optimal solution of the large-scale nonlinear constraint optimization.